Soft Law in Jus in Bello and Jus ad Bellum : What Lessons for Business and Human Rights? - Dunkelberg, Alonso Gurmendi (AJIL unbound, 2020)
This contribution, rather than focusing on the debates within the Business and Human Rights (BHR) domain itself, offers a comparison between soft law regulation in the BHR context, on the one hand, and in the jus in bello (JIB) and jus ad bellum (JAB) contexts, on the other. Specifically, this contribution looks at the recent experience in JIB and JAB wherein states and other actors have tried to address the indeterminacy of treaty law provisions through soft law proposals that advance a disputed interpretation of hard law, producing legal uncertainty and scholarly debate. I use as examples the 2009 Interpretive Guidance on Direct Participation in Hostilities and the 2012 Bethlehem Principles as a way to extract lessons for the codifying momentum underway in BHR.